Gestión de comunicación externa orientada a la imagen corporativa del instituto de estudios ecuatorianos a partir de sus proyectos sociales - Arregui Fernández de Córdova, Eloísa (2016)
The objective of the following dissertation is to propose a communicational scheme sustained on the General Systems Theory and which complies with the concepts studied in corporative communication. The General Systems Theory understands organizations and their actors as a whole where the exchange of actions and communication affects them both. This generates a cycle of interrelation between various systems, which at the same time creates one greater system that allows the autonomy of each part. This dissertation intends to trace a plan for the External Communication Management oriented to the image of the Instituto de Estudios Ecuatorianos, a non-governmental organization. This management strategy focuses on the social projects of the IEE for the investigation, formation and technical assistance to local development, addressed to indigenous peoples and nationalities, social organizations and the academy.